Presenting a foresight model in order to compile the vision of Isfahan city - Mahboobeh Khalafi; Naser Barati (مهندسی و مدیریت ساخت)
Nowadays, with the increase in urban population, a city with favorable conditions that can remain sustainable in all dimensions is considered. The increasing complexity of multiple elements in cities has made it difficult to assess the long-term future. Therefore, the need for a tool that, in addition to building capacity, prepares the society and decision-makers for issues and leads to the most favorable social benefit is felt. By creating a long-term vision, foresight leads to the generation of vision(s) that meet the level of expectations of citizens with their participation. This process is a solution to draw a picture for the future of cities (especially strategic cities) which, while providing solutions to today's challenges, guides managers in reaching a sustainable city for the future. The world famous city of Isfahan has undergone many demographic, power and ethnic changes and today it is facing issues such as pollution, drying up of Zayandeh Rood and subsidence of the land, corona disease, which despite its 25 years of history in traditional urban planning, it has not been able to is ready to face challenges. For this reason, in this research, the future forecasting model of this city is questioned in order to develop a vision. For this, first, by using the meta-combination method and examining 58 valid articles while extracting relevant themes for building a landscape with a foresight approach, by surveying and using the opinion of 26 experts in the field of future studies and urban planning, the components of the foresight framework were extracted in order to build a landscape. . In this research, the findings show that extracting strategic questions, managing stakeholders, and creating scenarios are important components of the landscape in the city of Isfahan.